An Analysis on the Speech Contestants’ Arguments in English Celebration Week - Raharja, Octaviyani (Journal of English Department WM, 2014)
Nowadays, many universities hold speech contest to facilitate their students in improving their communicative skills. Widya Mandala Catholic University, through English Department, holds a speech contest during the English Celebration Week event. As speech contest in common, students are required to conduct a good speech that deals with the topic given. Unfortunately, there are still some mistakes found that deal with the argument components and verbal fallacies. In figuring out a good speech, the contestants’ speeches are recorded and transcribed to be analyzed whether they have met the quality of a good speech which are: (1) includes all of the main components of argument and (2) fallacies free. Since the speech contestants are still in the first semester, they have limited knowledge on argument components and verbal fallacies. Therefore, the contestants sometimes miss the argument components and make no verbal fallacies in their speech.